Polymorphonuclear neutrophil leukocytes in snakebite envenoming - Zuliani, Juliana Pavan (2020)
Polymorphonuclear neutrophils are the most abundant leukocytes in the blood and constitute key components of the innate immunity. Upon infection or tissue damage, neutrophils are recruited to tissues, where they exert a variety of effects, such as microbicidal activity, phagocytosis, degranulation, formation of reactive oxygen species (ROS), release of inflammatory mediators, and formation of neutrophil extracellular traps (NETs). In addition to microbial killing and removal of damaged tissue components, neutrophils play a role in the resolution of inflammation and, in some circumstances, they stimulate chronic inflammation and may contribute to tissue damage. The participation of neutrophils in snakebite envenoming has been explored in the clinical and experimental settings. Clinically, envenomings are associated with increases in the numbers of circulating neutrophils, with a left shift. Experimentally, neutrophils are the first inflammatory cells to reach tissue injected with venoms or tissue-damaging toxins. Venoms and toxins induce several effects on neutrophils in vitro, including chemotaxis, activation, degranulation, synthesis of inflammatory mediators, generation of ROS, and formation of NETs. The role of neutrophils in the pathogenesis of venom-induced tissue damage has been explored, with variable results depending on the venom. In some cases, neutrophils play a key role in muscle regeneration following venom-induced myonecrosis. The processes involved in the recruitment and activation of neutrophils after injection of snake venoms and toxins, and the possible role of these leukocytes in envenomings, are discussed in this review.